2016
DOI: 10.1097/jpa.0000000000000082
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Team-Based Learning (TBL) on Physician Assistant Students' Academic Performance in Gross Anatomy

Abstract: Team-based learning is an effective supplement to cadaveric dissection. Student short-term knowledge outcomes improve with the combination of dissection and team-based learning in the gross anatomy laboratory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 8 publications
0
21
0
1
Order By: Relevance
“… three were randomised controlled trials (Kang et al, 2016; Kim et al, 2016; Sakamoto et al, 2020); 19 were pre‐test post‐test studies, of which ten had two‐groups (Cho & Kweon, 2017; Clark et al, 2008; Eun & Hye Young, 2017; Harmon & Hills, 2015; Hemmati Maslakpak et al, 2015; Kim & Kim, 2020; Koohestani & Baghcheghi, 2016; Lee, 2018; Mennenga, 2013; Seo & Roh, 2020) and nine had one group (Cheng, Liou, Hsu, et al, 2014; Cheng et al, 2014; Cho & Kweon, 2017; Goolsarran et al, 2018; Park et al, 2015; Roh et al, 2020; Siah et al, 2019; Whittaker, 2015; Wong et al, 2017); 10 were descriptive cohort studies (Corbridge et al, 2013; Ebrahimpour & Pelarak, 2016; Isbell et al, 2016; Mennenga, 2015; Roh et al, 2015) (Ouellette & Blount, 2015; Ulrich et al, 2017) (Considine et al, 2014; Currey et al, 2018; Miles et al, 2017); six studies used mixed methods (Branney & Priego‐Hernández, 2018; Considine et al, 2014; Currey, Oldland, et al, 2015; Feingold et al, 2008; McRae et al, 2017; Morris, 2016); and three were qualitative studies (Currey, Eustace, et al, 2015; Göktepe et al, 2018; Oldland et al, 2017). …”
Section: Resultsmentioning
confidence: 99%
“… three were randomised controlled trials (Kang et al, 2016; Kim et al, 2016; Sakamoto et al, 2020); 19 were pre‐test post‐test studies, of which ten had two‐groups (Cho & Kweon, 2017; Clark et al, 2008; Eun & Hye Young, 2017; Harmon & Hills, 2015; Hemmati Maslakpak et al, 2015; Kim & Kim, 2020; Koohestani & Baghcheghi, 2016; Lee, 2018; Mennenga, 2013; Seo & Roh, 2020) and nine had one group (Cheng, Liou, Hsu, et al, 2014; Cheng et al, 2014; Cho & Kweon, 2017; Goolsarran et al, 2018; Park et al, 2015; Roh et al, 2020; Siah et al, 2019; Whittaker, 2015; Wong et al, 2017); 10 were descriptive cohort studies (Corbridge et al, 2013; Ebrahimpour & Pelarak, 2016; Isbell et al, 2016; Mennenga, 2015; Roh et al, 2015) (Ouellette & Blount, 2015; Ulrich et al, 2017) (Considine et al, 2014; Currey et al, 2018; Miles et al, 2017); six studies used mixed methods (Branney & Priego‐Hernández, 2018; Considine et al, 2014; Currey, Oldland, et al, 2015; Feingold et al, 2008; McRae et al, 2017; Morris, 2016); and three were qualitative studies (Currey, Eustace, et al, 2015; Göktepe et al, 2018; Oldland et al, 2017). …”
Section: Resultsmentioning
confidence: 99%
“…Additionally, based on previous studies, 22 we designed some clinical cases based on the anatomy textbook and tried to include the questions on major anatomical and clinical knowledge. The results showed that TBL method could significantly improve the examination scores than TL, which is in accordance with the previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…• Provides an opportunity to expose students to interprofessional education (e.g., between medical, midwifery, nursing, physician assistant, physical therapy, and occupational therapy students) (Fernandes et al, 2015). • Creates a setting conducive to team-based learning (Huitt et al, 2015;Isbell et al, 2016), near-peer teaching, (Durán et al, 2012;Reyes-Hernandez et al, 2015;Agius et al, 2018;Alvarez and Schultz, 2019;Kinirons et al, 2019;Viana et al, 2019) reciprocal peer teaching (Hendelman and Boss, 1986;Brueckner and MacPherson, 2004;Krych et al, 2005;Bentley and Hill, 2009;Pizzimenti et al, 2016;Manyama et al, 2016;Agius et al, 2018;Kinirons et al, 2019), and flipped classroom pedagogy (Day, 2018;Fleagle et al, 2018). • Fits well into an integrated curriculum, with the potential to meaningfully incorporate disciplines such as dermatology (Baker et al, 2014;Yang et al, 2018), interventional radiology (DePietro et al, 2017), and pathology (Geldenhuys et al, 2016;Rae et al, 2017).…”
Section: Should Human Gross Anatomical Dissection Be Performed?--the mentioning
confidence: 99%